Penerapan Protokol MQTT pada Sistem Akuakultur Berbasis Internet of Things - Fikri, Teuku Adam; Nasir, Muhammad; Rudi F, Fachri Yanuar; Taufik, Taufik (Politeknik Negeri Lhokseumawe, 2023)
Aquaculture are used to increase the production of aquatic organisms for rearing, harvesting, processing and marketing in fish farming. However, currently the supervision of the aquaculture system is still carried out conventionally by monitoring and controlling directly to the cultivation location so that it is considered ineffective, especially in terms of time. The goal to be achieved in this study is the application of the MQTT protocol to the aquaculture system by knowing the percentage of error values for each sensor and the average time delay obtained from the results of data transmission. The system created can monitor, provide feed and monitor water quality. The main devices needed in this system consist of a Raspberry Pi as a system controller, a temperature sensor to measure water temperature, a Turbidity sensor to measure the level of water turbidity and a Ph sensor to measure the acidity level of the water. The results obtained in this study are the MQTT protocol can be applied with the percentage error value on the sensor from 0,07% - 0,67% and the average delay time is 2,43 seconds.Keywords— Aquaculture, MQTT, Monitoring, pH Sensor, Turbidity Sensor, Temperature Sensor, Ultrasonik Sensor, Raspberry Pi